Corporate Governance and Performance of Reits : The Study of Singapore and Malaysia - Khoo, Kok Chen (2015)
As more countries in Asia are introducing real estate investment trusts to facilitate capital inflows into their respective real estate market, the issues of corporate governance has inevitably become a major attention of real estate investors. The study has three objectives which are to test the effectiveness of corporate governance mechanisms of the S-REITs and M-REITs between 2008 and 2013, to identify the corporate governance attribute that contributes best towards R-Index scores and to test whether R-Index scores contribute to better performance of the REITs. The study’s overall objective is to investigate the relationship between corporate governance and performance of REITs in Singapore and Malaysia. The descriptive analysis indicates that the standard of corporate governance in both S-REITs and M-REITs have been improved from 2008 through 2013 as the market size grows bigger. The results of correlation analysis show that all attributes in the R-Index except Ownership are significantly correlated with the total score of R-Index. Finally, regression analyses are conducted to test whether R-Index scores contribute to better performance of the REITs in Malaysia and Singapore. In the ROE model, we find the relationship between the structure of corporate governance and ROE is insignificant. The lack of relationship between corporate governance and ROE is possibly due to the “REIT effect” as the unique operating characteristics of REITs and legal setting under which the REITs operate may help mitigate the potential agency problems, thereby reducing the importance of corporate governance in REITs. In the ROA model, the regression results show that R-Index, firm size and financial leverage have a significant relationship with ROA. However, the significant negative relationship between R-Index and ROA contrasts with our expectation. We explain that this relationship is more relevant for loss-making REITs in our sample in practical scenario because the loss-making REITs need a more effective mechanism of internal control in order to gain investor confidence and obtain financial assistance which are crucial for turnaround and improving investment returns.